Controlling of electro-optical properties of cobalt phthalocyanine formed single chain polymer: Sudan III and nanographene based its composites - Demirelli, Kadir; Barim, Esra; Tuncer, Hulya; Dere, Aysegul; Canbay, Canan Aksu; Karaduman, Oktay; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
The synthesis of poly[4-(4-vinylbenzyl)oxy)phthalonitrile-co-styrene] [P(VBOPN5 %-co-St)] was carried out by free radical polymerisation at 60 degrees C. The successful formation of a green coloured single -chain polymer molecule with the formation of cobalt phthalocyanine (SCP-CoPc) was performed at 140-150 degrees C in the presence of dilute cyclohexanol. The characterization of SCP-CoPc was confirmed by FT -IR and UV/vis spectroscopic techniques. The absorption filtration process of the SCP-CoPc polymer/Sudan III composite was investigated. The introduction of Sudan III into the SCP-CoPc polymer matric strongly affected the optical transmission spectrum of the composite films. The optical transmission measurements of the SCP-CoPc/Sudan III thin film show a high absorption in the visible region (400-800 nm). In the SCP-CoPc/Sudan III composites, the optical band gaps (Eg1 and Eg2) of each of its components has changed significantly. The Eg1 and Eg2 were found to be between 1.90 and 2.83 eV, respectively. Depending on the sudan III content, a wide range from 600 nm to 730 nm indicates complete absorption filtration. The dc electrical conductivity and dielectric behavior of the SCP-CoPc/ Nanografene (NG) 6 wt% nanocomposite increased with increasing temperature. From the dc conductivity plot, the Ea values of I. and II. regions were found to be 0.75 eV and 0.27 eV, respectively and it was found that the calculated activation energy obeyed the Arrhenius relationship. The refractive index and the optical permittivity of SCP-CoPc/NG 6 wt% have been estimated.
Keywords: Single-chain polymer; Cobalt phthalocyanine; Optical properties; Composite; Nanographene; Electrical properties